Genetic Evidence of Focal Plasmodium falciparum Transmission in a Pre-elimination Setting in Southern Province, Zambia. (16th November 2018) - Pringle, Julia C; Tessema, Sofonias; Wesolowski, Amy; Chen, Anna; Murphy, Maxwell; Carpi, Giovanna; Shields, Timothy M; Hamapumbu, Harry; Searle, Kelly M; Kobayashi, Tamaki; Katowa, Ben; Musonda, Michael; et al.
Abstract: Background: Southern Province, Zambia has experienced a dramatic decline in Plasmodium falciparum malaria transmission in the past decade and is targeted for elimination. Zambia's National Malaria Elimination Program recommends reactive case detection (RCD) within 140 m of index households to enhance surveillance and eliminate remaining transmission foci. Methods: To evaluate whether RCD captures local transmission, we genotyped 26 microsatellites from 106 samples collected from index (n = 27) and secondary (n = 79) cases detected through RCD in the Macha Hospital catchment area between January 2015 and April 2016. Results: Participants from the same RCD event harbored more genetically related parasites than those from different RCD events, suggesting that RCD captures, at least in part, infections related through local transmission. Related parasites clustered in space and time, up to at least 250 m from index households. Spatial analysis identified a putative focal transmission hotspot. Conclusions: The current RCD strategy detects focal transmission events, although programmatic guidelines to screen within 140 m of index households may fail to capture all secondary cases. This study highlights the utility of parasite genetic data in assessing programmatic interventions, and similar approaches may be useful to malaria elimination programs seeking to tailor intervention strategies to the underlying transmission epidemiology. Abstract : Microsatellite genotyping from Plasmodium falciparum samples collected during reactive case detection in Macha, Zambia, revealed temporal-spatial clustering of genetically related parasites. Relatedness extended at least 250 m from index households, suggesting that the current 140-m screening radius misses secondary cases.